A Review Study on the Influence and Impact of Knowledge Management Practices on the Performance and Growth of SMEs - Muraleedharan, Nikhil Vimala; Velmurugan, Vellaiyan Perumal (International Review of Management and Marketing, 2026)
Knowledge management (KM) plays a critical role in enhancing the performance and growth of small and medium-sized enterprises (SMEs), yet challenges such as limited resources, technological adoption, and informal knowledge practices hinder effective knowledge utilization. This review investigates the influence of KM practices, absorptive capacity, and innovation strategy on SME performance, providing a structured framework for understanding their interrelationships. A systematic literature review was conducted using databases including Scopus, Web of Science, and Google Scholar, applying inclusion and exclusion criteria to identify high-quality studies relevant to SMEs. The review highlights that KM practices encompassing knowledge creation, sharing, storage, and application positively impact operational efficiency, innovation, customer satisfaction, and strategic decision-making. Absorptive capacity acts as a mediator, transforming knowledge into actionable insights, while innovation strategy aligns KM initiatives with organizational objectives, enabling sustainable growth. Technology-enabled KM tools, including digital platforms, cloud systems, and emerging AI and blockchain solutions, further enhance knowledge accessibility, integration, and utilization. The synthesized insights culminate in a conceptual framework linking KM practices to SME performance, illustrating pathways through which knowledge-driven mechanisms foster competitiveness and growth. This study contributes theoretically by integrating mediating and enabling mechanisms into SME KM literature and practically by offering guidance for managers, policymakers, and KM system developers. Future research directions include empirical testing of KM frameworks, exploring contextual variations, and investigating technology-enabled solutions to strengthen absorptive capacity and innovation in SMEs. Overall, the study underscores the strategic importance of knowledge management for sustainable SME performance and growth.